VIOLÊNCIA NA TORCIDA ORGANIZADA DE FUTEBOL: ESTUDO DE CASO DA TORCIDA TREM FANTASMA (2009-2013) - Lara, Luiz Marcelo de (2014)
Sport plays an important role in development of society, acting as an object of identifying individuals, as we can see in football. Football is a field in which individuals notice a moment to live in groups, especially as fans. This dissertation aims to understand the role of violence in football organized cheer, with the understanding of how these groups of fans are formed. In Brazil, soccer is very present in the social context, in which different individuals can participate in various ways, from athletes to fans. However, that sport in its modern features allows us to visualize situations in which violence is established in a certain way and in a certain sense. We used the theoretical framework of Norbert Elias for understanding society. The methodological approach takes as its point of departure, using semi-structured interview, because it is a case study of an organized cheer of the city of Ponta Grossa, the Trem Fantasma Cheer of Operário Ferroviário Sport Club. Violence is present in organized groups of football, but in relation to these supporters we observed the category in some moments, not in a significantly way.